LEARNERS' PERSPECTIVES ON USING THE FORVO WEBSITE AS A STRATEGY TO ENHANCE SPEAKING SKILLS - Zaki, Alwan Ammar; Hermansyah; Jaya, Aswadi (Universitas PGRI Palembang, 2024)
This qualitative case study investigated learners’ perspectives on using the Forvo website to enhance their English-speaking skills within an online Discord community,